Research on the path of social psychological collaborative education in colleges and universities driven by the dynamic reward and punishment mechanism of the government - Jingjia Guo; Yang Gao; Fangcheng Tang (PLoS ONE, 2026)
This study addresses the prevalent issues of “coordination failure” and “cooperative inertia” in the collaborative education of mental health between universities and society. Utilizing evolutionary game theory, it systematically constructs and analyzes four models that combine government rewards and punishments. The findings indicate that while the traditional static reward and punishment mechanism offers basic incentives, its rigid design results in the system’s path dependence on government subsidies, thereby hindering the development of sustainable endogenous motivation. In order to address this governance dilemma, this paper first put forward the idea of combining “performance-based grant-reputation incentive” linkage system, this mechanism has prompted the external incentives to the internal incentives transformation effect under the joint governance of short-term fiscal policy and long-term reputation asset through the dynamic adjustment of incentive coefficient and reputation incentive resources are put into use. Numerical simulation results show that the “dynamic reward - static punishment” hybrid model of the two has the best policy effect. In the initial stage of cooperative relationship, government funding helps to break the situation of cooperation cannot be broken; In the later stage of the cooperation, the pursuit of reputation capital has become the motive for cooperating in deeper. It can be learned from relevant studies that reasonably allocating more incentive resources to universities that take the initiative can significantly enhance the efficiency of the system evolving into the state of deep cooperation and open sharing. Both theoretical and empirical evidence confirms that the proposed dynamic linkage mechanism markedly outperforms the traditional static model in terms of policy adaptability, incentive sustainability, and institutional robustness. This finding not only enriches the understanding of the evolutionary dynamics of the psychological healthy education system but also provides a theoretical foundation and practical pathway for establishing an incentivized, compatible, and sustainable governance system for mental health education.